Perancangan Sistem Clustering Susu Sapi dengan Menggunakan Metode K-Means - Lestari, Duwi Pungki; , Yusuf Sulistyo Nugroho, S.T.,M.Eng (2016)
Abstract Along with the development of information technology very rapidly, making many people to use it. Many information technologyused to help facilitate the work of man. In the field of animal husbandry, cattle to be bred in great demand because it has many benefits one of them milk. Milk is a product of processed animal proteins produced cows. The milk produced by farmers and then sold to a KUD (villagr unit cooperative) which is a reservoir of milk will be processed. A KUD can have many kinds of milk is based on content owned so much data can be obtained. So that a classification system should be developed to help dairy cooperatives dairy segment data based on similar data as well as member information if there is a new data entry. The system was developed by utilizing an algorithm K-Means clustering algorithm which is one of data mining to perform a grouping. Grouping is done in maximum system is divided into 3 groups, with the variables used are protein, fat, solid non fat and total solid. Results from this study is an application system that can assist in classifying milk cooperatives based on similar data using the KMeans algorithm so that the training data help can be made into multiple clusters. The results showed that, if the system is used to make 1 group, the results: cluster 1 with a dot centroid (3.072; 3.715; 8,070; 11,785), if made 2 groups then the result: cluster 1 with a dot centroid ( 3,017 ; 3,508 ; 7,937 ; 11,445 ) and cluster 2 with point centroid ( 3,109 ; 3,856 ; 8,160 ; 12,016), while if made 3 groups then the result: cluster 1 with a dot centroid centroid ( 3,040 ; 3,827 ; 8,071 ; 11,898)and cluster 2 with point centroid ( 3,424 ; 3,922 ; 8,487 ; 12,409 ) also cluster 3 with centroid point ( 3,015 ; 3,456 ; 7,933 ; 11,389 ). Keyword : Clustering, Data Mining, K-means, KUD (Village Unit Cooperative), Milk.